Examining the Role of Uganda Christian University Focus Television on Empowering Female Student Leaders - Felista Nshakimana (Uganda Christian University, 2026)
This research focused on the effect of UCU Focus TV on the empowerment of female student leaders at Uganda Christian University, Mukono. The study sought to determine the extent to which the television station affects the empowerment process, the problems encountered, and the potential recommendations for improvement. The results showed that UCU Focus TV is a platform that gives female students a voice to share their opinions and experiences in leadership. The programs that have been aired have boosted the confidence and participation of women in the university community. The problems that were encountered include lack of airtime, gender biases, and insufficient media skills. The study recommends that UCU Focus TV should produce more balanced and educational programs for the empowerment of female students.
Undergraduate